Prediction and Comparison of Fentanyl Infusion Pharmacokinetics in Obese and Nonobese Children. Issue 12 (December 2019) - Lim, Sin Yin; Woo, Sukyung; Miller, Jamie L.; Skrepnek, Grant H.; Henry, Emilie D.; Johnson, Peter N.
Abstract : Objectives: To compare fentanyl infusion pharmacokinetic variables in obese children and nonobese children. Design: A pharmacokinetic simulation study. Setting: We used a semi-physiologically based pharmacokinetic model to generate fentanyl pharmacokinetic variables. Subjects: Simulations of pharmacokinetic variables were based on historical inpatient demographic data in less than 18-year-olds. Interventions: Obese children were defined as children less than 2 years with weight-for-length greater than or equal to 97.7th percentile or body mass index-for-age greater than or equal to 95th percentile for greater than or equal to 2–17-year-olds. Measurements and Main Results: Overall, 4, 376 patients were included, with 807 (18.4%) classified as obese children. The majority (52.9%) were male, with a median age of 8.1 years (interquartile range, 4.3–13.0 yr). The differences in total clearance (CLS ), volume of distribution at steady-state values, weight-normalized CLS, and weight-normalized volume of distribution at steady state were assessed in obese children and nonobese children. Multivariable analyses indicated that obesity was significantly associated with a higher CLS in obese children greater than 6-year-olds ( p < 0.0375). However, there was an 11–30% decrease in weight-normalized CLS in obese children versus nonobese children in all age groups ( p < 0.05). Both volume of distribution at steady state and weight-normalized volume of distribution at steady state increased significantly in obese children compared with nonobese children ( p < 0.05). Fentanyl plasma concentration-time profiles of obese children and nonobese children pairs (ages 4, 9, and 15) receiving 1 µg/kg/hr using total body weight were also compared. Steady-state concentrations of the obese children using similar weight-based dosing increased by 25%, 77%, and 44% in comparison to nonobese children 4-, 9-, and 15-year-olds, respectively. Time to steady state and elimination half-lives were two- to four-fold longer in obese children. An additional simulation was conducted for 15-year-old obese children and nonobese children using a fixed dose of 50 µg/hr and it provided similar pharmacokinetic profiles. Conclusions: CLS may increase less than proportional to weight in obese children greater than 6-year-olds, while volume of distribution at steady state increases more than proportional to weight in all obese children compared with nonobese children. Weight-based dosing in obese children may cause an increase in steady-state concentration while prolonging the time to steady state. Exploring alternative dosing strategies for obese children is warranted. Abstract : Supplemental Digital Content is available in the text.